ESTADO Y SEGURIDAD PRIVADA EN COSTA RICA. ANÁLISIS DE COYUNTURA. - Muñoz Guillén, Mercedes (2025)
Study of the link between the State and private security companies in Costa Rica, in order to answer the following questions: How much is invested in the juncture 2006-2008 to keep the offer of this service in some instances of the public sector? How does the accounting reflect the amounts that the State invests on services of private monitoring, as an expense or an investment? And  why is the geographic expansion of private security  partly the result of its link with the State?